Mechanized cassava production - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2018)
Mechanization is key to take Agric-business to another level, however it is important to follow the right step and technical-know-how to be able achieve the best of mechanization, this video demonstrates the important steps to follow in mechanization of cassava production for potential investors in the sector.